Identification of differentially expressed genes and pathways in isonuclear kenaf genotypes under salt stress. Issue 4 (18th November 2020) - Munsif, Fazal; Kong, Xiangjun; Khan, Aziz; Shah, Tariq; Arif, Muhammad; Jahangir, Muhammad; Akhtar, Kashif; Tang, Danfeng; Zheng, Jie; Liao, Xiaofang; Faisal, Shah; Ali, Izhar; et al.
Abstract: Salinity is a potential abiotic stress and globally threatens crop productivity. However, the molecular mechanisms underlying salt stress tolerance with respect to cytoplasmic effect, gene expression, and metabolism pathway under salt stress have not yet been reported in isonuclear kenaf genotypes. To fill this knowledge gap, growth, physiological, biochemical, transcriptome, and cytoplasm changes in kenaf cytoplasmic male sterile (CMS) line (P3A) and its iso‐nuclear maintainer line (P3B) under 200 mM sodium chloride (NaCl) stress and control conditions were analyzed. Salt stress significantly reduced leaf soluble protein, soluble sugars, proline, chlorophyll content, antioxidant enzymatic activity, and induced oxidative damage in terms of higher MDA contents in both genotypes. The reduction of these parameters resulted in a reduced plant growth compared with control. However, P3A was relatively more tolerant to salt stress than P3B. This tolerance of P3A was further confirmed by improved physio‐biochemical traits under salt stress conditions. Transcriptome analysis showed that 4256 differentially expressed genes (DEGs) between the two genotypes under salt stress were identified. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that photosynthesis, photosynthesis antenna‐protein, and plant hormone signal transduction pathways might be associated with the improved NaCl stress tolerance in P3A. Conclusively, P3A cytoplasmic male sterile could be a potential salt‐tolerant material for future breeding program of kenaf and can be used for phytoremediation of salt‐affected soils. These data provide a valuable resource on the cytoplasmic effect of salt‐responsive genes in kenaf and salt stress tolerance in kenaf.